THE WORLD OF LIFE BEHIND PAYLATER TRANSACTIONS HABERMAS' PERSPECTIVE: BETWEEN RATIONALITY AND VISIBLE NEEDS - Rini Novita Sari; Windi Komala Sari (Program Studi Sosiologi Universitas Malikussaleh, 2026)
Humans cannot be separated from science and technology, as technology has become a necessity. The rapid development of communication today impacts all aspects of human life, including e-commerce, which has been significantly driven by the digital transformation over the past decade. On the one hand, technology aims to make life easier for humans, but on the other hand, humans are sometimes faced with dilemmas regarding life's necessities. This article uses a qualitative method, utilizing Jürgen Habermas's theory of human needs and consumption. The author collected and published various literature sources, including scientific journals and research reports, using data such as Google Scholar and Scopus with relevant keywords. Literature selection was based on relevance, credibility, and year of publication. This study examines the challenges facing humans with technological developments and changing times. Rational awareness can be used to make choices in social reality. Strong rational and critical awareness and financial literacy are necessary to navigate the digital consumption system. Consumers need to develop a reflective and rational attitude in making financial decisions, so that technologies like PayLater do not become tools that obscure life values, but remain guided by ethics and true needs.